Evaluation of parental mitochondrial inheritance in neonates born after intracytoplasmic sperm injection. - Danan, C (1999)
Intracytoplasmic sperm injection (ICSI) is now used when severe male-factor infertility has been documented. Since defective mitochondrial functions may result in male hypofertility, it is of prime importance to evaluate the risk of paternal transmission of an mtDNA defect to neonates. DNA samples from the blood of 21 infertile couples and their 27 neonates born after ICSI were studied. The highly polymorphic mtDNA D-loop region was analyzed by four PCR-based approaches. With denaturing gradient gel electrophoresis (DGGE), which allows 2% of a minor mtDNA species to be detected, the 27 newborns had a DGGE pattern identical to that of their mother but different from that of their father. Heteroplasmy documented in several parents and children supported an exclusive maternal inheritance of mtDNA. The parental origin of the children's mtDNA molecules also was studied by more-sensitive assays: restriction-endonuclease analysis (REA) of alpha[32P]-radiolabeled PCR products; paternal-specific PCR assay; and depletion of maternal mtDNA, followed by REA. We did not detect paternal mtDNA in nine neonates, with a sensitivity level of 0.01% in five children, 0.1% in two children, and 1% in two children. The estimated ratio of sperm-to-oocyte mtDNA molecules in humans is 0.1%-1.5%. Thus, we conclude that, in these families, the ICSI procedure performed with mature spermatozoa did not alter the uniparental pattern of inheritance of mtDNA.